(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
Brachystelma seshachalamense, a new species belonging to the family Apocynaceae, is described from the Seshachalam hills of Kadapa District of Andhra Pradesh, India. The new species is closely allied to Brachystelma beddomei Hook. f., but differs in usually solitary flowers, corolla tube large with a ring of hairs around the corona, corolla lobes spreading with white hairy along the margins and pubescent inside, coronal cup lemon yellow, interstaminal corona shallowly lobed with hairs. Bangladesh J. Plant Taxon. 23(1): 53-57, 2016 (June)